Evaluation of leukocytes cells types counts in blood from patients with different severities of periodontal diseases - Chinar J Ali; Nada K Imran; Maha A Ahmed (College of Dentistry/ University of Baghdad, 2023)
Background: Periodontal diseases are inflammatory disorders caused by the accumulation of oral biofilm and the host response to this accumulation which characterized by exaggerated leukocytes and neutrophils attraction to the sites of inflammation by chemoattractants which are a very important part of the pathogenesis of periodontal diseases. This study aimed to determine and compare the clinical periodontal parameters and the leukocyte cell types in the peripheral blood between patients with gingivitis and periodontitis with different severities compared to healthy controls. Materials and methods: This study included 150 male subjects aged between 35-50 years. They were divided into three groups: gingivitis group (n=30), periodontitis patients (n=90) which subdivided into Mild =30 patients, Moderate =30 patients, Severe =30 patients and a control group (n=30) with clinically healthy periodontium. Clinical periodontal parameters were recorded ((plaque index (PLI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL)). Blood samples were collected then an automated blood analyzer evaluated leukocyte cell types. Results: Significant differences in The counts of neutrophils and lymphocytes exhibited significant differences among the study groups and subgroups. On contrary, differences in monocytes, eosinophils, and basophils counts were not significant. Additionally, severity of periosontitis was significantly correlated with the mean counts of the various leukocyte cell types; however, clinical periodontal characteristics did not show such correlation with these inflammatory cells. Conclusion: This study demonstrated that periodontal disease with different severities is associated with possible episodes of bacteremia that originate from periodontal lesions which mediate inflammatory conditions that in turn causing changes in the systemic markers especially leukocytes cells types.